Pengaruh Kombinasi Pupuk Organik dan Hayati Terhadap Pertumbuhan dan Produksi Galur Jagung (Zea mays. L) Hasil Seleksi Efisien hara Pada Lahan Kering Marginal - Yopie Moelyohadi; M. Umar Harun; Munandar Munandar; Renih Hayati; Nuni Gofar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
This study aimed to study the growth and yield of maize crop nutrient efficient selection against the combination of different types of organic fertilizers and bio-fertilizers at low dose levels of chemical fertilizer on marginal dry land for the development of technological innovation fertilization on maize crops to reduce the use of chemical fertilizer on marginal dry land. This study was conducted in the field trials of Agro Techno Park (ATP), the Ministry of Research and Technology, South Sumatra from January to May 2012. The experimental design used was SplitPlotdesign with three replications. . The main plot treatment was dose levels of chemical fertilizer consists of : P1 = 50 % standard dose of ATP ( 200 kg urea , 50 kg SP36 and 25 kg KCl/ha ) and P2 = 25 % standard dose of ATP ( 100 kg urea , 25 kg SP36 KCl and 1.25 kg/ha) . treatment subplot , is the combined delivery of this type of organic fertilizer + biofertilizer types , comprising : KHO = control ( without organic fertilizer + biofertilizer ) , KH1 = composted cow manure + mycorrhiza , KH2 = composted cow manure + bacterial phosphate solvent , KH3 = composted chicken manure + biological mycorrhizae , KH4 = composted chicken manure + bacterial phosphate solvent , KH5 = compost straw corn + mycorrhizae , KH6= composted maize straw + bacteria phosphate solvent , KH7 = compost Legume cover crop ( LCC ) + Mycorrhiza and compost KH 8= legume cover crop (LCC) + solvent bacteria Phosphate. The results showed that chicken manure compost fertilizer + fertilizer mycorrhizal give the best effect on the growth and yield of dryland corn yields marginal with an average of 9.70 tons of dry cobs/ha and the combined treatment of chemical fertilizer at 50 % level and composting chicken manure + mycorrhizal give the best effect on the growth and yield of maize in marginal dry land , with an average yield reached 10.51 tons of dry seed/acre.